Pediatric Gastrointestinal Endoscopy: Diagnostic Yield and Appropriateness of Referral Based on Clinical Presentation: A Pilot Study - Fachler, Tahel; Shteyer, Eyal; Orlanski Meyer, Esther; Shemasna, Ibrahim; Lev Tzion, Raffi; Rachman, Yelena; Bergwerk, Ari; Turner, Dan; Ledder, Oren (Frontiers in Pediatrics, 2021)
Objectives: There is a lack of evidence-based consensus for the utility of gastrointestinal endoscopy (GIE) in an array of frequently occurring symptoms in children. We aimed to assess the diagnostic yield of endoscopy in an effort to aid clinical decision making. Methods: Retrospective analysis of patients ≤18 years who underwent GIE during one calendar year at Shaare Zedek Medical Center. We excluded children referred for pre-defined obvious indications for GIE, planned follow-up procedures and therapeutic endoscopy. Clinician-assigned indication for endoscopy, as well as endoscopic and histologic findings were recorded. Diagnostic yield of GIE was determined according to referral indication. Results: 794 endoscopies were performed of which 329 were included in the analysis (mean age 9.3 ± 5.0 years, 51% female). No significant complications of GIE were recorded. Six major referral indications were identified amongst which abdominal pain was the most frequent 88/329 (26%), of whom 32/88 (36%) had a significant diagnostic finding. Amongst the other major indications, diagnostic findings were found in 36/85 (43%) children with primary indication of chronic diarrhea, 14/33 (42%) failure to thrive (FTT), 15/32 (46%) short stature, 30/56 (54%) iron deficiency, and 20/48 (42%) weight loss. Conclusions: Pediatric GIE is a safe procedure with diverse clinical indications. The diagnostic yield of endoscopy is variable, depending on the referral indication. These data can assist formulating judicious referral practices.